Effects of microbial phytase on apparent retention of phosphorus, calcium and zinc in broilers according to type of diet - Pérez-Vendrell A.M.; Angulo E.; Brufau J. (Feed manufacturing in the Mediterranean region. Improving safety: From feed to food, 2001)
Two basal diets were used, based on maize-soybean (6 U endogenous phytase per kg) or in wheat-soybean (410). Eight experimental treatments were tested. Statistical significant differences in AME of diets between treatments were not found. Animals fed P-deficient diets showed higher apparent retention and better bioavaliability of all evaluated minerals. The addition of phytase enzyme to maize diets produced statistically significant increases in mineral bioavailability (P less than 0.0001 for total phosphorus; P less than 0.0026 for phytate phosphorus; P less than 0.0151 for calcium; and P less than 0.0224 for zinc). In wheat diets, only total and phytate phosphorus bioavailabilities were improved by phytase addition (P less than 0.0010).
3. Conference of Feed Manufacturers of the Mediterranean, 2000/03/22-24, Reus (Spain)